Optimalisasi Penerapan Metode Pembelajaran Berbasis Al-Quran dalam Meningkatkan Kualitas Pendidikan Islam - Fitriyyah, Rofii’atul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research aims to optimize the implementation of Quran-based learning methods to enhance the quality of Islamic education. The research methodology includes literature study, where the researcher relies on various literature to obtain research data and employs a qualitative approach since the data produced is in the form of words or descriptions. The main focus of this study is to examine Quranic learning methods in schools that are structured and designed using verses from the Quran as the primary foundation for delivering learning materials. Several findings regarding the Quranic learning methods used by teachers in the classroom include the amtsal method, lecture method, and discussion method. Additionally, verses from the Quran are used as a source of inspiration in developing relevant methods, strategies, and learning media related to the material being taught. More importantly, the application of values contained in the Quran, such as honesty, justice, patience, and others, in the learning process, both directly and integrated into the learning material, is emphasized. The research findings indicate that the implementation of Quran-based learning methods can improve the quality of students' learning. Setting clear memorization targets, conducting muroja’ah (revision), and using interactive learning techniques, such as discussions, have proven effective in strengthening students' memorization. Overall, this research underscores the importance of adapting Quran-based learning methods to meet students' needs, thereby enhancing the overall quality of Islamic education.